La succión: una actividad erótica - Nelson Cortes-Castaño (Universidad de Antioquia, 2000)
For the dentist the oral cavity has meaned just an anatomical site 01the total human body, in it thereare located the organs on which he or she practices his or her biotechnological knowledge. From Freud on thepsychoanalytic school olthought proposed that the mouth is an erogenouszone full otlibido around it thesubjectdisplayshis or her pulsion and it represents his or her history; elso, thesuction activity notonly lulfill a nutritional lunction but it is an erotic activity that tends toseek pleasure in this particular zone 01the body, cover by mucous on lips and mouth.